Women in the fiction of Rabindranath Tagore - Krishna Iyer, Mangala Bhavani; Quayum, Mohammad Abdul (IIUM Press, International Islamic University Malaysia, 2017)
This book examines selected works of a larger than life literary figure, Rabindranath Tagore (1861-1941), with a special focus on his female characters. Works selected for the study are novels Binodini (1903), Gora (1909), The Home and the World (1916) and The Broken Nest (1921), as well as several short stories. A visionary and a social reformist, Tagore, among several other sociocultural, political and religious issues that he addressed in his works, recurrently sought to resort the circumstances of women as mothers, wives and child brides in his fictional writings. As an expression of this, he portrayed all his female characters, especially in the works selected for this study, in a new and convincing style, by consciously and conspicuously moving away from tradition and age-old conventions. Tagore spoke of and felt the need for women to be seen and heard beyond the home. His sympathy for child brides and widows are showcased extensively in many of these narratives. He categorically rejected the traditional concept where women were expected to be confined to the zenana. His passion for freedom was so far and wide that he felt that the liberation and freedom given to men should also be extended to women. He said that women had that natural expression to her, a cadence of restraint in her behaviour, producing poetry of life. She has been an inspiration to man, guiding, often unconsciously, his restless energy into an immense variety of creations in literature, art, music and religion. In the process, justifying the need of women to be liberated from the shackles of home, Tagore rejected all forms of religious extremism and cultural conservatism. This book also examines selected Hindu scriptures to examine how the effects of blind conformity to these scriptures had resulted in women being enslaved, bound and bonded by men in the name of social progress and stability. In the book we have highlighted how women can be both good at home and at the same time extend their radiance beyond home so that they grow intellectually. In doing so, Indian women discover their self-worth as individuals and find agency in their being, moving away from the shadow of the men. This is Tagore’s unique prescription for the emancipation of women, who were otherwise living in a hierarchical, andocentric social system.